Europäische Aviation-Studie. Stellhebel für profitables Wachstum im Luftverkehr. - Elders, Volker; Koch, Stefan (Deutscher Verkehrs-Verl., 2007)
Die Situation in der Luftfahrt hat sich in den vergangenen Jahren dramatisch verändert. Zwar können sich die Fluggesellschaften seit 2003 wieder über ansteigende Passagierzahlen freuen, sehen sich andererseits aber durch steigende Kerosinpreise und zunehmenden Wettbewerbsdruck von Low Cost Carriern mit beschleunigtem Margenverfall konfrontiert und müssen um die Früchte der Restrukturierungsbemühungen der jüngsten Zeit fürchten. Auch die Flughäfen sind betroffen, denn sie müssen sich der Bewältigung aufgebauter Überkapazitäten stellen und können andererseits einen andauernden Preisverfall bei Flughafengebühren kaum verhindern. Die Lösungsansätze sehen auf beiden Seiten ähnlich aus: Fokussierung auf das Kerngeschäft und gleichzeitiges Outsourcing von Randbereichen. difu

This study is based on a survey amongst 48 top managers of airlines and airports. The survey was developed and conducted by the International Management Consultancy Droege & Comp. Key objectives were to highlight market insiders' opinions arising from an intensified competitive market environment and to show which measures market players implement to react to such changes and developments in order to prevail in the long run. The results of the study can be summarized as follows: The aviation industry is characterized by two seemingly contradictory developments. Sustainable growth of demand for air travel is offset by rising costs of fuel procurement and an intensified price pressure triggered by the market entry of low cost carriers. The growth rate curve of recent years is flattening. Excess capacities arise and cannot be absorbed by the market in the mid- and long run. The airlines are forced to effectively improve cost structures and to optimize their organizational system as well as decision making processes. This will cause an increasing number of mergers and thereby consolidate the market. At the same time international alliances will prevail as the most important Global Players. Predominantly small aviation companies will find themselves obliged to clearly position themselves in one of three business segments - low cost carrier, network-airline, or regional carrier. Airports are also exposed to the mentioned market developments as they will be exposed to the pressure passed on to them by airlines. Excess capacities that also have evolved amongst airports make a clear orientation towards a specific business model - Hub, low-cost-carrier, or point-to-point - indispensable. The necessity of generating new revenue in the non aviation business is of increasing importance in either case. difu
Keywords: Verkehr; Luftverkehr; Marktanteil; Flughafen; Ertrag; Wettbewerb; Fluggesellschaft; Outsourcing; Verkehrsmarkt; Tarif